2019
DOI: 10.1097/prs.0000000000006072
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Reconstruction Using the Integra Dermal Regeneration Template

Abstract: Summary: The reconstruction of nasal defects following oncologic resection has traditionally involved the use of locoregional flaps or full-thickness skin grafts. However, these options are not always feasible because of limitations in donor tissues, defect size or shape, oncologic issues, or patient preference. Reconstruction in this setting has been limited and unsatisfactory. In this report, the authors present their experience in reconstruction of nasal defects using the dermal regeneration tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…For patients for whom the single-stage procedure occurred due to patient non-compliance (patients 2 and 4), we reported significant re-epithelialization with new skin formation, despite the extreme non-compliance. All 4 patients did not develop contractures, as previously reported for single-stage re-epithelialization using IBWM [ 28 ]. In addition, we reported in one patient (patient 4), dermal appendages such as hair follicles had returned.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…For patients for whom the single-stage procedure occurred due to patient non-compliance (patients 2 and 4), we reported significant re-epithelialization with new skin formation, despite the extreme non-compliance. All 4 patients did not develop contractures, as previously reported for single-stage re-epithelialization using IBWM [ 28 ]. In addition, we reported in one patient (patient 4), dermal appendages such as hair follicles had returned.…”
Section: Discussionsupporting
confidence: 71%
“…The most common reason for single-stage reconstruction with re-epithelialization was patient preference to avoid an autologous reconstruction, followed by large defect size/depth. Average time for complete re-epithelialization was 1.5 ± 0.8 months [ 28 ]. For patients for whom the single-stage procedure was conducted due to patient preference (patients 1 and 3), these patients were monitored closely during the re-epithelialization process, and followed medical advices and indications for wound management.…”
Section: Discussionmentioning
confidence: 99%
“…47 Another case series assessing the use of Integra for nasal defects after oncological resection demonstrated that while Integra was effective as a treatment modality, postoperative complications including contour deformity (18.8%), hyperpigmentation (12.5%), and alar retraction (12.5%) were observed. 49…”
Section: Integramentioning
confidence: 99%
“…Various methods have been used in nasal reconstruction, ranging from dermal regeneration (integra) [6], skin grafts, as well as a wide variety of flaps; The nasolabial flap, frontal flap and the frontonasal flap are recognized as the main pillars in nasal reconstruction [7].…”
Section: Introductionmentioning
confidence: 99%